Hubungan Tingkat Pengetahuan dan Sikap Remaja Putri tentang Seksual Pra Nikah di SMA Negeri "Y" Kota Batam Tahun 2016 - Erika Fariningsih (Jurnal Surya Medika (JSM), 2021)
Premarital sexual behavior in adolescents is all behavior that is driven by the desire teenager well with the opposite sex or same-sex committed before their official relationship as husband and wife. Sexual objects could be someone else, people in the delusion, or self. Kinds of premarital sex among other things: kissing, necking, petting, intercourse. About 54% of the teenage single women had lost their virginity. The purpose of this study is to determine the relationship between Knowledge and Attitudes of Young Women With Pre-Marital Sexual Behavior In SMAN “Y” Batam 2016. In research using quantitative research with an analytical design using the cross-sectional approach, the samples of research use Probability Sampling Methods and techniques Simple Sampling with 218 respondents. The results of the research are most of the respondents have good knowledge about sexual behavior before marriage as many as 211 respondents (96.8%) and a positive attitude about the premarital sexual behavior of 132 respondents (60.6%). From the results of Chi-Square test knowledge study is p-value 0,001 > 0,05 and attitudes p-value 0.002 > 0.05. The conclusion of this research is There are Relationship Knowledge and Attitudes About Sexual Behaviour of Young Women Pre Marital In SMAN “Y” Batam.